2007
DOI: 10.1039/b618920b
|View full text |Cite
|
Sign up to set email alerts
|

Efficient proton conduction in dry nanofilms of amorphous aluminosilicate

Abstract: Amorphous aluminosilicate nanofilms as prepared by a sol-gel process and post-annealing exhibit proton conduction at a wide temperature range in dry air with a lowest area specific resistance of 0.24 omega cm2 at 400 degrees C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
24
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 24 publications
3
24
0
Order By: Relevance
“…Recently, we discovered that silica-based, nanometer-thick films gave high proton conductivity at 100-400°C under nonhumidified atmosphere due to formation of stable Brønsted acid sites when doped with some other metal ions. 4,5 Especially, the aluminosilicate, Al x Si 1−x O n , nanofilm showed the highest proton conductivity and revealed practically usable levels of ASR at around 300°C.5 Several other research groups reported that the ion conductivity of multilayered materials increased with decreasing layer thickness. 6,7 These studies prompted us to study the effect of thickness for our Al x Si 1−x O n film.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we discovered that silica-based, nanometer-thick films gave high proton conductivity at 100-400°C under nonhumidified atmosphere due to formation of stable Brønsted acid sites when doped with some other metal ions. 4,5 Especially, the aluminosilicate, Al x Si 1−x O n , nanofilm showed the highest proton conductivity and revealed practically usable levels of ASR at around 300°C.5 Several other research groups reported that the ion conductivity of multilayered materials increased with decreasing layer thickness. 6,7 These studies prompted us to study the effect of thickness for our Al x Si 1−x O n film.…”
mentioning
confidence: 99%
“…These films are composed commonly of homogeneously mixed glasses without phase separation, as checked by transmission electron microscopy observation. 4,5 Al/Si atomic ratio of the film was determined by X-ray photoelectron spectroscopy ͑XPS͒. Before XPS measurement, the surface layer ͑a few tens of nanometers thick͒ of sample was sputtered by Ar + ion so as to form a clean surface and probe the inner area of the films.…”
mentioning
confidence: 99%
“…We recently applied this method to preparation of amorphous aluminosilicate nanofilm and found that this nanometer-thick film is a practically useful proton conductor with area-specific resistance of 0.2 V cm 2 at 400 8C in dry atmosphere. [9] In order to evaluate such unique proton conductivity, it is important to see if similar proton conductivity is observed with other silica-based metal oxides. These materials would be useful as electrolyte membranes if they could be fabricated into ultrathin membranes that are nonpermeable toward neutral gas molecules; hydrogen and oxygen, since silica is one of the most stable matrix under electrochemical conditions.…”
mentioning
confidence: 99%
“…In our preliminary experiments, an aluminosilicate film of 100-nm thickness prepared from a 100 mM mixed sol of AlCl 3 and tetraethoxysilane (TEOS) with atomic ratio of Al/Si ¼ 0.1/0.9 in ethanol showed a conductivity two orders of magnitude lower than that of a corresponding film (Al 0.18 Si 0.82 O 1.91 ), prepared from a 100 mM mixed sol of aluminum tri-sec-butoxide and TEOS in 1-propanol in a previous study. [9] Therefore, it was essential to employ identical conditions to compare ion conductivity of different silica-based oxide films. In this study, we decided to conduct a multiple spin-coating approach for very dilute precursor sols of TEOS and metal alkoxides [M(OR) n ] in 1-propanol, since this precursor preparation was applicable to a wide variety of silica-based, double-oxide films.…”
mentioning
confidence: 99%
“…Recently, high density and defect-free thin oxide films free from organic species have been fabricated by a layer-by-layer sol-gel processing and the obtained thin films revealed interesting properties as dielectric 36,37 and proton-conducting materials. 38,39 In the layer-bylayer sol-gel processing, the thickness of the film developed by one processing cycle was less than 10 nm. Thus, layer-by-layer deposition of nm-thick oxide films is also of interest as a protective layer for corrosion protection.…”
mentioning
confidence: 99%